DESAIN SISTEM PEMBUMIAN DENGAN PEMBERIAN ZAT ADITIF GYPSUM DAN GARAM PADA GEDUNG UNIT GAWAT DARURAT RUMAH SAKIT BALI MANDARA - Pramana Putra, I Made Randi Dwi; Harta Narayana, Made Agus Putra; Alit Swamardika, Ida Bagus; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
In the Bali Mandara Hospital Emergency Unit Building the soil resistivity is quite high, making it difficult to install a grounding system with a lower soil resistivity value according to the standard. This study aims to determine the effectiveness of adding gypsum and salt additives in reducing soil resistivity. The method used is quantitative descriptive which is carried out directly. The results of this study with the addition of gypsum and salt additives are effective in reducing soil resistivity at Bali Mandara Regional Hospital. The soil resistivity value without additives is 33 , 912 ???? .m with a measurement value of 0 , 27 ohm. The soil resistivity value with gypsum additives is 26.376 ???? .m with a measurement value of 0 ,21 ohm, there is a decrease of 7 , 54 ???? .m (22 , 2%). The soil resistivity value with salt additives is 30 , 144 ???? .m with a measurement value of 0.24 ohm, there is a decrease of 3 , 768 ???? .m (11 , 1%). The right grounding system to be used in Bali Mandara Hospital with sandy soil texture is to use a single rod type grounding resistance without additives, at a cost of Rp 5 . 680 . 400 using 42 electrode rods. The grounding resistance obtained by using the single rod type is 0.941886 ohms with a depth of 50 meters.